Необхідність забезпечення справедливості ефірного часу для багатошвидкісних мереж IEEE 802.11 - Токар, Л. О.; Греков, І. С.; Колтаков, О. А. (ХНУРЕ, 2021)
It is considered that with the simultaneous operation of two or more wireless users, which differ in speed performance, the phenomena of air monopolization appear, which is reflected in the imperfection of the built-in mechanisms of the IEEE 802.11 standard and the distribution of air time. Today's relevance of this issue raises one of the critical problems for wireless performance, which is expressed in the monopolization of airtime by slow users. It is shown that the tasks of increasing the efficiency and equitable distribution of channel resources between competing nodes are solved at different levels of the network. Methods and ways of fair distribution of airtime in multi-rate wireless networks based on both the use of algorithms and mechanisms for accessing the air and hardware implementations have been analyzed.
Keywords: Необхідність забезпечення; Мережі IEEE